1996
DOI: 10.1523/jneurosci.16-01-00019.1996
|View full text |Cite
|
Sign up to set email alerts
|

Selective alterations in gene expression for NMDA receptor subunits in prefrontal cortex of schizophrenics

Abstract: NMDA receptor antagonists can induce a schizophrenia-like psychosis, but the role of NMDA receptors in the pathophysiology of schizophrenia remains unclear. Expression patterns of mRNAs for five NMDA receptor subunits (NR1/NR2A-D) were determined by in situ hybridization in prefrontal, parieto-temporal, and cerebellar cortex of brains from schizophrenics and from neuroleptic-treated and nonmedicated controls. In the cerebral cortex of both schizophrenics and controls, mRNAs for NR1, NR2A, NR2B, and NR2D subuni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
218
4
3

Year Published

1998
1998
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(234 citation statements)
references
References 62 publications
9
218
4
3
Order By: Relevance
“…35,37 These studies found no changes in transcript expression for NR2A, NR2B and NR2D, a small but significant decrease for NR2C in the frontal cortex in schizophrenia, and identified increased transcript expression for NR2A and PSD-95 in occipital cortex. 35 In addition, these studies reported either increased or unchanged expression of the NR1 transcript, which might be attributed to a difference in the prefrontal cortical area studied (Brodmann area 10 vs 46).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…35,37 These studies found no changes in transcript expression for NR2A, NR2B and NR2D, a small but significant decrease for NR2C in the frontal cortex in schizophrenia, and identified increased transcript expression for NR2A and PSD-95 in occipital cortex. 35 In addition, these studies reported either increased or unchanged expression of the NR1 transcript, which might be attributed to a difference in the prefrontal cortical area studied (Brodmann area 10 vs 46).…”
Section: Discussionmentioning
confidence: 98%
“…[31][32][33][34] Changes in the expression of transcripts encoding NMDA receptor subunits in the prefrontal cortex have previously been described in post-mortem schizophrenic brains. [35][36][37] However, relatively little is known about protein expression of these subunits in schizophrenia. Additionally, expression of the NMDA receptor-interacting PSD molecules in schizophrenia have to date only been analyzed on transcriptional level, and primarily in subcortical regions in post-mortem brain.…”
Section: Introductionmentioning
confidence: 99%
“…The preponderance of these studies has detected complex and regionally specific alterations in ␣ -amino-3-hydroxy-5-methyl-4-isoxazolepropionate (AMPA), kainate, and N-methyl-D-aspartate (NMDA) receptor expression, especially in cingulate cortex and medial temporal lobe structures (Akbarian et al 1996;Aparicio-Legarza et al 1998;Deakin et al 1989;Eastwood et al 1997aEastwood et al , 1997bEastwood et al , 1995Grimwood et al 1999;Harrison et al 1991;Healy et al 1998;Humphries et al 1996;Ibrahim et al 2000;Kerwin et al 1988Kerwin et al , 1990Kornhuber et al 1989; MeadorWoodruff and Healy 2000;Nishikawa et al 1983;Noga et al 1997;Ohnuma et al 1998;Porter et al 1997;Sokolov 1998). Recently, such studies have been extended to other brain regions associated with limbic circuitry felt to be disturbed in psychiatric illnesses, including the striatum.…”
Section: Because Abnormalities Of Glutamatergic Neurotransmission In mentioning
confidence: 99%
“…Involvement of sigma receptors in the action of ketamine is unlikely, because the behavioral effects of ketamine correlate with NMDA, but not sigma, receptor binding affinity (Ginski and Witkin 1994). The presence of glutamatergically mediated psychotomimetic effects of ketamine is also congruent with histological (Benes et al 1991;Benes et al 1992;Benes 1995;Simpson et al 1991;Ishimaru et al 1994;Akbarian et al 1996) and neuroimaging (Bartha et al 1997) evidence for glutamatergic abnormalities in schizophrenia (see also Olney and Farber 1995).…”
mentioning
confidence: 95%